Predictive analytics : the power to predict who will click, buy, lie, or die - Siegel, Eric, 1968- (New Jersey : Wiley, 2016)
"Predictive analytics unleashes the power of data. With this technology, computers literally learn from data how to predict future behaviors of individuals. In this updated and revised edition of Predictive Analytics, former Columbia University professor and Predictive Analytics World founder Eric Siegel reveals the power and perils of prediction. New material includes: - The Real Reason the NSA Wants Your Data: Automatic Suspect Discovery. A special sidebar in Chapter 2, "With Power Comes Responsibility," presumes--with much evidence--that the National Security Agency considers PA a strategic priority. Can the organization use PA without endangering civil liberties? - Dozens of new examples from Facebook, Hopper, Shell, Uber, UPS, the U.S. government, and more. The Central Tables' compendium of mini-case studies has grown to 182 entries, including breaking examples. - A much needed warning regarding bad science. Chapter 3, "The Data Effect," includes an in-depth section about an all-too-common pitfall, and how we avoid it, i.e., how to successfully tap data's potential without being fooled by random noise, ensuring sound discoveries are made. - Even more extensive Notes, updated and expanded to 70+ pages, now moved to an online PDF. Now located at www.predictivenotes.com, the Notes include citations and comments that cover the above new content, as well as new citations for many other topics"--
Includes index.
Keywords: Social sciences -- Forecasting; Economic forecasting; Prediction (Psychology); Social prediction; Human behavior; BUSINESS & ECONOMICS / Consumer Behavior; BUSINESS & ECONOMICS / Econometrics; BUSINESS & ECONOMICS / Marketing / General